Changing food environments in Africa's urban and peri-urban areas: Implications for diets, nutrition, and policy - Katrin Glatzel; Hannah Ameye; Vivien Hülsen; Matin Qaim (University of Bonn, Center for Development Research (ZEF), 2024)
Driven by urbanization and demographic changes with a growing middle class and more economically active women, food environments are changing across the African continent with important dietary consequences on a region already contending with the triple burden of malnutrition. Over the past two decades, African countries have experienced rapid growth in the number and spread of supermarkets making (ultra)processed foods available at all times and in convenient and attractive forms that align with consumers' changing lifestyles and timeuse. The demand for processed foods (of all types) is expected to continue to rise over the next decades, presenting both challenges and opportunities. Carefully crafted policies, incentive structures, and regulations are powerful tools through which to address 'food entry points', and factors influencing consumer choices including the availability, affordability, accessibility, and desirability of foods. The paper further examines how food environments are changing and adapting in two African countries, Tanzania and Malawi. Drawing on data collected in five regions in Tanzania and six districts in Malawi, the findings provide important insights into how food consumption patterns and dietary health vary between rural and urban areas.
Keywords: 330